Análisis de la ejecución presupuestaria de ingresos Del Gobierno Autónomo Descentralizado Municipal del cantón Alfredo Baquerizo Moreno (Jujan), en el año 2020 - Acosta Molina, Julissa Beatriz (2021)
This case study prepared in Canton Alfredo Baquerizo Moreno (Jujan), province of Guayas has as its theme "Analysis of the budget execution of revenues of the Municipal Decentralized Autonomous Government of Canton Alfredo Baquerizo Moreno (Jujan) in the year 2020", where budgetary information is presented on the revenues collected in that period, which have had a significant reduction compared to the initial allocation. The study is carried out through the application of financial tools such as vertical and horizontal analysis, to the current, capital and financing revenues presented in the municipal entity's income statement, budget management indicators are used to determine the level of efficiency and effectiveness of revenues and the calculation of budget financial indicators is also applied. The methodology applied in this case study is the inductive method, in addition, information was obtained through an interview with the Financial Director and the collection of documentary information presented by the Municipal Decentralized Autonomous Government of Canton Alfredo Baquerizo Moreno (Jujan), which in this case are the budgetary income statements for the year 2020. All this information is complemented with bibliographic data consulted in books, laws, scientific journals and other sources.